Benzolamide improves oxygenation and reduces acute mountain sickness during a high‐altitude trek and has fewer side effects than acetazolamide at sea level - Collier, David J. (Pharmacol Res Perspect, 2016)
Acetazolamide is the standard carbonic anhydrase (CA) inhibitor used for acute mountain sickness (AMS), however some of its undesirable effects are related to intracellular penetrance into many tissues, including across the blood–brain barrier. Benzolamide is a much more hydrophilic inhibitor, which nonetheless retains a strong renal action to engender a metabolic acidosis and ventilatory stimulus that improves oxygenation at high altitude and reduces AMS. We tested the effectiveness of benzolamide versus placebo in a first field study of the drug as prophylaxis for AMS during an ascent to the Everest Base Camp (5340 m). In two other studies performed at sea level to test side effect differences between acetazolamide and benzolamide, we assessed physiological actions and psychomotor side effects of two doses of acetazolamide (250 and 1000 mg) in one group of healthy subjects and in another group compared acetazolamide (500 mg), benzolamide (200 mg) and lorazepam (2 mg) as an active comparator for central nervous system (CNS) effects. At high altitude, benzolamide‐treated subjects maintained better arterial oxygenation at all altitudes (3–6% higher at all altitudes above 4200 m) than placebo‐treated subjects and reduced AMS severity by roughly 50%. We found benzolamide had fewer side effects, some of which are symptoms of AMS, than any of the acetazolamide doses in Studies 1 and 2, but equal physiological effects on renal function. The psychomotor side effects of acetazolamide were dose dependent. We conclude that benzolamide is very effective for AMS prophylaxis. With its lesser CNS effects, benzolamide may be superior to acetazolamide, in part, because some of the side effects of acetazolamide may contribute to and be mistaken for AMS.